STRATEGI MEMBANGUN KAMPUNG WISATA BERBASIS BUDAYA LOKAL DI DESA WATORUMBE KECAMATAN MAWASANGKA TENGAH KABUPATEN BUTON TENGAH - Munsir Munsir; Syamsumarlin Syamsumarlin; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
The purpose of this research is to describe the strategy of tourism village building in Watorumbe Village, Central Mawasangka District, Central of Buton Regency based on local culture. To answer that purpose, data collection is done through observation and interview, and the data obtained is analyzed descriptively qualitative. The adaptation theory of John W. Bennet, an adaptation as a human survival strategy. The research method used by choosing the location of research, selection of informants, data collection techniques, and data analysis techniques. So guiding the author to find answers to research problems. The results showed that in the development of tourism village, there are certain strategies that must be done to make the village of Watorumbe as a tourist village. The strategies are (1) having a togetherness in the social structure of watorumbe, (2) preserving traditional cultural values, (3) disseminating the culture of Watorumbe society to society, (4) development of facilities and infrastructure, and (5) art-culture studio community.